2017
DOI: 10.15376/biores.13.1.981-996
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Chimeric Lipase-cutinase (Lip-Cut) for Efficient Enzymatic Deinking of Waste Paper

Abstract: Lipase and cutinase belong to the esterase family and have biological applications in many fields. To develop more efficient biocatalysts that can be used for waste paper deinking, a chimeric lipase-cutinase (LipCut) was constructed and successfully overexpressed in Pichia pastoris. The chimeric Lip-Cut exhibited lipase and cutinase activities that were 127% and 210% higher than their parent enzymes, respectively. Cut was superior to Lip in ink removal and improvement of paper brightness than Lip. The Lip-Cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Reactions with MtCUT were conducted in pH 7.5 at 30 • C for 3 h, and they resulted in ink removal rates of close to 80% for both types of paper. Liu and coworkers studied the efficiency of T. terrestris cutinase and Thermomyces lanuginosus lipase for the deinking of laser-printed paper and newspaper pulps [136]. Researchers first noticed that even though lipase had very low activity on PVAc, there seemed to be a synergistic effect between the two enzymes.…”
Section: Other Bioremediation Applicationsmentioning
confidence: 99%
“…Reactions with MtCUT were conducted in pH 7.5 at 30 • C for 3 h, and they resulted in ink removal rates of close to 80% for both types of paper. Liu and coworkers studied the efficiency of T. terrestris cutinase and Thermomyces lanuginosus lipase for the deinking of laser-printed paper and newspaper pulps [136]. Researchers first noticed that even though lipase had very low activity on PVAc, there seemed to be a synergistic effect between the two enzymes.…”
Section: Other Bioremediation Applicationsmentioning
confidence: 99%
“…Despite the similarities, an important difference is the width of the active site cleft, in comparison with cutinase from TfH; this slot is three times larger at its widest point in PETase ( Austin et al, 2018 ). Furthermore, the residues surrounding the nucleophilic serine in the catalytic triad were found to be considerably different, which affects the substrate selectivity represented by these enzymes ( Liu et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the regions on the surface outside the active site of the enzymes and binding modules are essential, both in interaction with the polymer and during the hydrolysis ( Acero et al, 2013 ). For instance, Liu et al (2018a) assumed in their study that the wide substrate-binding pocket of PETase is critical for PET hydrolysis ( Liu et al, 2018b ). In contrast, Austin et al (2018) narrowed the binding cleft and observed improvement in PET degradation ( Austin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations